Holocene Sedimentary Environment of the Atlantic Inner Shelf Off Delaware. - Sheridan,R. E.; Dill,C. E. , Jr.; Kraft,J. C. (1974)
High-resolution subbottom profiles and Vibracoring off the Delaware coast confirm the partial retention of Holocene coastal environments under the inner shelf. The Holocene transgression has involved erosion through the Holocene lagoonal sediments in some areas, leaving pre-Holocene ridges exposed on the inner-shelf sea floor where once there may have been headlands. The ancient lagoonal deposits are thickest over depressions in the pre-Holocene surface. The presence of marsh peat, dated as approximately 7,500 yr. B.P., and overlying very fine lagoonal mud proves that lagoonal conditions existed east of Delaware even then. The bottom morphological features of the inner shelf off Delaware are related to dynamic molding of hydraulic bedforms in equilibrium with the present marine environment. Although one ridge form was found to be a subcrop of Pleistocene sand and gravel, most of the ridge and channel topography was found to be formed within the upper Holocene sediments. This is especially true of the shorefaceconnected ridges off Rehoboth Bay and Bethany Beach, the inlet-associated shoals near the mouth of Delaware Bay, and the Delaware shelf-valley flood channel.